Periostin action in bone. (5th September 2016) - Bonnet, Nicolas; Garnero, Patrick; Ferrari, Serge
Abstract: Periostin is a highly conserved matricellular protein that shares close homology with the insect cell adhesion molecule fasciclin 1. Periostin is expressed in a broad range of tissues including the skeleton, where it serves both as a structural molecule of the bone matrix and a signaling molecule through integrin receptors and Wnt-beta-catenin pathways whereby it stimulates osteoblast functions and bone formation. The development of periostin null mice has allowed to elucidate the crucial role of periostin on dentinogenesis and osteogenesis, as well as on the skeletal response to mechanical loading and parathyroid hormone. The use of circulating periostin as a potential clinical biomarker has been explored in different non skeletal conditions. These include cancers and more specifically in the metastasis process, respiratory diseases such as asthma, kidney failure, renal injury and cardiac infarction. In postmenopausal osteoporosis, serum levels have been shown to predict the risk of fracture-more specifically non-vertebral- independently of bone mineral density. Because of its preferential localization in cortical bone and periosteal tissue, it can be speculated that serum periostin may be a marker of cortical bone metabolism, although additional studies are clearly needed. Highlights: Periostin is a highly conserved matricellular protein. Periostin activates integrin -Akt-FAK-β catenin signaling pathway. Periostin has multifaceted role in bone homeostasis. Periostin is a key factor in bone formation response to loading and PTH. Periostin may be a new serum bone biomarker in osteoporosis.